Neutral and adaptive variation in the most widely distributed native tree species in Patagonia: on the way to defining provenance regions for Nothofagus pumilio - Mattera, María Gabriela; Torres, Ana Delia; Soliani, Carolina; Aparicio, Alejandro Gabriel; Marchelli, Paula; Pastorino, Mario Juan (2018)
In our ongoing project, we aim to define Provenance Regions (PR) for the species along its distribution range in Argentina, from 36º S to 55º S. We propose the combination of neutral genetic variation with quantitative information generated from common garden provenance and progeny genetic trials.